Rapid and simultaneous multiepitope antigen-based detection of Enterococcus by microscale thermophoresis and immunomagnetic separation - Liu, Yan; Wang, Ziyan; Wang, Ze; Zhou, Jun; Han, Jiaojiao; Lu, Chenyang; Liu, Bing; Yu, Rongxian; Sun, Xiaoling; Zhang, Zhen; Wang, Rixin; Su, Xiurong (Frontiers in Microbiology, 2024)
Background Generally, enterococci bacteria cause nosocomial infections and are major indicators of bacterial contamination in marine bathing beach. However, a method for the rapid and simultaneous detection of multiple pathogenic enterococci has not been developed on account of the wide variety of pathogenic enterococci and their existence in complex matrices. Methods Immunoinformatics tools were used to design a multi-epitope antigen for the detection of various pathogenic enterococci by using the sequence of dltD gene on enterococci lipoteichoic acid (LTA) surface, which is associated with toxicological effects. The multi-epitopes included enterococci such as Enterococcus faecalis, E. gallinarum, E. raffinosus, E. durans, E. faecium, E. hirae, E. thailandicus, E. casseliflavus, E. avium, E. mundtii, E. lactis, E. solitarius, E. pseudoavium, and E. malodoratum. Microscale thermophoresis (MST) and western blot were carried out to detect the affinity between multi-epitope antigens and antibodies and between multi-epitope antibodies and bacteria. Furthermore, the detection of pathogenic enterococci was carried out by using immunomagnetic beads (IMBs) and immune chromatographic test strip (ICTS). Results The multi-epitope antibody had a satisfactory affinity to the antigen and enterococci. IMBs and ICTS were detected with a minimum of 101 CFU/mL and showed incompatibility for Vibrio parahemolyticus, V. vulnifcus, V. harveyi, V. anguillarum, and Edwardsiella tarda. Implication The present study demonstrated that the multi-epitope antigens exhibited excellent specificity and sensitivity, making them highly suitable for efficient on-site screening of enterococci bacteria in marine bathing beaches.